Kualitas Pelayanan Publik Pada Pelayanan Surat Keterangan Usaha Di Kantor Kelurahan Perawang - Kamelia Nuzul, Salwah; Rahman, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
The purpose of this study was to determine how the quality of public services on business certificate services at the Perawang Village office. The theory in this study uses Zeithaml's theory of public service quality with five indicators, namely Tangible Evidence, Reliability, Responsiveness, Assurance, and Empathy. The method used is descriptive qualitative method, and data collection techniques through observation, interviews, and documentation. With data analysis using data reduction, data presentation and conclusion drawing. The results found from this study indicate that the business certificate service at the Perawang Village office has not provided quality service.